CRITICAL ANALYSIS OF ENVIRONMENTAL HEALTH POLICIES AND ASSESSING IMPLEMENTATION, ENFORCEMENT, AND PUBLIC HEALTH IMPACT OF REGULATIONS AIMED AT ENSURING FOOD SAFETY - Turki Hussain Mohammed Alsharyah, Fahad Hadi Alsharyah, Muqrin Hussain Alsharyah, Munasslr Dhafer Mohammed Al Sharyh, Mesfer Hussain Binali Al Sharyah, Hamad Hussain Mohammed Alsharyah, Salem Hadi Ali Alsharya (Chelonian Research Foundation, 2022)
Environmental health policy is of the utmost importance regarding public health, where the policies focus on the safety of foods. A holistic examination to judge the adequacy of the establishment, execution, enforcement, and impact on public health of environmental health policies that ensure food security is done. To conduct an in-depth analysis of the existing literature, case studies, and empirical research, the paper explores the effectiveness of regulatory frameworks, the enforcement challenges encountered, and a thorough look at their influence on public health outcomes. Also, the paper for evaluating the implementation and enforcement of the food safety regulation strategies is discussed, as are the opportunities for dealing with public health issues while keeping policy interventions in mind. The main factors considered are the urgent need for efficient supervision mechanisms, the need for contributions from both the health and food industry sectors and the importance of involving the communities. Keywords: Environmental public, food safety, require, implementation,